Disjointed modes of building resilience to socio-environmental crises - Anna Salomaa; Tapio Reinekoski; Henna Salminen; Kelsey Krivochenitser; Janne I Hukkinen; Turo-Kimmo Lehtonen (Ecology and Society)
Socio-environmental crises are bound to worsen and bring about unprecedented uncertainties regarding their anticipation and management. We studied how public organizations in Finland build resilience to such crises (that is, the capacity needed to deal with and recover from disruptions) and how and why their efforts appear dysfunctional in the face of worsening crises. Our data-driven qualitative analysis draws on interviews with 58 experts in Finnish public organizations in different fields of service provision. We find that resilience is built in three distinct yet interacting modes: Mode 1, as operational action and readiness; Mode 2, as prevention and planning; and Mode 3, as exploring and sketching the unknown. These modes are distinguishable from one another by features such as severity of disruptions, temporal scales of operation, degrees of uncertainty, actionability of measures and attribution of responsibilities, and ways of knowing the future. Based on our analysis of how the modes interact, we diagnose a mutual disconnect between Modes 2 and 3. The demands that the latter imposes on planning and modeling find little grounding in current practices in Finnish public organizations. Conversely, operations in Mode 1 and Mode 2 can be so institutionally locked in that they end up constraining the ability to account for and adapt to any threats beyond tried-and-true methods. It is this disjointedness that, we suggest, permits socio-environmental crises to creep in. We encourage scholars and practitioners to inquire into and identify similar disconnects that can turn aspirations for resilience in organizational practices against themselves. Not only could this elucidate the different kinds of efforts to build resilience in and across governance domains, but it would also help identify whether established practices are able to incorporate uncertainties that can be conjectured but not known for certain.